Spatial distribution of corticospinal potentials following transcranial electric and magnetic stimulation in human spinal cord - Kaneko, Kazuo; Kawai, Shinya; Taguchi, Toshihiko; Fuchigami, Yasunori; Morita, Hideki; Ofuji, Akira; Yonemura, Hiroshi (Journal of the Neurological Sciences, 1997)
To investigate the spatial distribution of the human corticospinal tract in the spinal cord, evoked spinal cord potentials (ESCPs) following transcranial electrical and magnetic stimulation were recorded simultaneously from both the anterior and posterior epidural space in five anesthetized patients. One ESCP component following transcranial electrical stimulation (D-wave) and at least two ESCP components (initially D-wave and later I-wave) following transcranial magnetic stimulation were recorded in all subjects. The negative peak latency of all the potentials recorded from the posterior epidural space was the same as that recorded anteriorly. The amplitude ratio of the ESCP following electrical stimulation (posterior/anterior) was 1.10±0.12, while that of ESCPs following magnetic stimulation was 1.08±0.12 (N1) and 1.15±0.16 (N2). These results suggest that lateral corticospinal tract descending dorsolateral fasciculus in the spinal cord is main corticospinal pathway and spatial distribution of D and I-waves are similar in the human cervical cord.